Etiological, epidemiological, and clinical features of acute diarrhea in China - Li-Ping Wang (Nature Portfolio, 2021)
Diarrhoea is a major cause of morbidity and mortality in China. Here, the authors present results from a large sentinel surveillance scheme from 217 hospitals in all 31 provinces in mainland China, including ~150,000 patients with acute diarrhoea and covering years 2009-2018.